2016
DOI: 10.1108/jrme-07-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Bricolage in the marketing efforts of a social enterprise

Abstract: Structured AbstractPurpose -The article aims to understand how resource constraints are addressed in the development of a marketing strategy by a social enterprise.Methodology -The authors have used an in-depth case study of collaboration between a Finnish university and an Indian social enterprise as the methodology for our research in which the data were collected over a period of two years. The data involve semi-structured interviews, field notes and student reports.Findings -The authors propose bricolage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Desa (2012) suggests that, in the face of resource constraints and sometimes penurious environments, social entrepreneurs are adept at mobilizing resources like the enterprising bricoleurs first described by Levi-Straus (1966), by making do with materials and pre-existing resources to achieve their goals. This observation was confirmed by the work of Kannampuzha and Suoranta (2016), whose case study of a health venture in rural India described entrepreneurs drawing upon an existing collaboration with a university for professional and personal contacts to "shatter" resource constraints. Although the study concentrates on the early stages of a social enterprise, utilizes only one example as its basis, and concentrates on existing sources, it offers a valuable insight into the mechanisms employed and the central role of networks in social enterprises.…”
mentioning
confidence: 75%
“…Desa (2012) suggests that, in the face of resource constraints and sometimes penurious environments, social entrepreneurs are adept at mobilizing resources like the enterprising bricoleurs first described by Levi-Straus (1966), by making do with materials and pre-existing resources to achieve their goals. This observation was confirmed by the work of Kannampuzha and Suoranta (2016), whose case study of a health venture in rural India described entrepreneurs drawing upon an existing collaboration with a university for professional and personal contacts to "shatter" resource constraints. Although the study concentrates on the early stages of a social enterprise, utilizes only one example as its basis, and concentrates on existing sources, it offers a valuable insight into the mechanisms employed and the central role of networks in social enterprises.…”
mentioning
confidence: 75%
“…Multiple case study Andersson et al, 2018;Pitchayadol et al, 2018;Toghraee et al, 2017;Weerawardena et al, 2017;Yang & Gabrielsson 2017;Renton, et al, 2015;Franco et al, 2014;Hallbäck & Gabrielsson 2013;Özdemir 2013;Bettiol et al, 2012;Mort et al, 2012;Szabo et al, 2011;Phua & Jones 2010;Schmengler & Kraus 2010;Jones & Rowley 2009;Moriarty et al, 2008;Perks & Shukla 2008 Single case study Crick et al, 2018;Fillis et al, 2017;Dalecki 2016;Kannampuzha & Suoranta 2016;Lewis et al, 2014;Lehman et al, 2014;Thomas et al, 2013;Meyers & Harmeling 2011;Gaddefors & Anderson 2009 Simple qualitative (without specifying design/method)…”
Section: Methods Studiesmentioning
confidence: 99%
“…The context in which EM has been investigated, varies from one study to another depending on the gaps the authors have found in the literature and contributed to cover that, and type of problems and businesses. It has been found that all the studies have investigated the businesses which were well established and present at least from few years except two studies (i.e., Kannampuzha & Suoranta 2016;and Meyers & Harmeling 2011) which have investigated the business start-up phase. Another key finding of this review is, most of the studies were focusing on success factors and marketing activities of successful businesses, but no study in the review is investigating the factors of failure or problems and challenges (e.g., Amjad et al, 2020) faced by the entrepreneurs during the journey of achieving that success.…”
Section: Findings Gap 1: Problem Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The SE is categorized by a plethora of business models (Bull, 2018) and is an ever‐expanding, ever‐developing, and “increasingly popular intervention” (Weaver, 2016, p. 4) that focuses on social value creation (Kannampuzha & Suoranta, 2016). SE focuses on local needs rather than on the “centralized assumptions of large institutions” (Seelos & Mair, 2005, p. 243), combining social and financial concerns as a symbiotic relationship representative of a business hybrid (Bradford, Luke, & Furneaux, 2018) in which profit is utilized to ameliorate, negate, and eradicate social ills.…”
Section: Review Of the Literaturementioning
confidence: 99%